A combined gas-phase dissociative ionization, dissociative electron attachment and deposition study on the potential FEBID precursor [Au(CH3)2Cl]2 - Bilgilisoy, Elif; Kamali, Ali; Gentner, Thomas; Ballmann, Gerd; Harder, Sjoerd; Steinrück, Hans-Peter; Marbach, Hubertus; Ingólfsson, Oddur (Beilstein Journal of Nanotechnology, 2023)
Motivated by the potential of focused-electron-beam-induced deposition (FEBID) in the fabrication of functional gold nanostructures for application in plasmonic and detector technology, we conducted a comprehensive study on [Au(CH3)2Cl]2 as a potential precursor for such depositions. Fundamental electron-induced dissociation processes were studied under single collision conditions, and the composition and morphology of FEBID deposits fabricated in an ultrahigh-vacuum (UHV) chamber were explored on different surfaces and at varied beam currents. In the gas phase, dissociative ionization was found to lead to significant carbon loss from this precursor, and about 50% of the chlorine was on average removed per dissociative ionization incident. On the other hand, in dissociative electron attachment, no chlorine was removed from the parent molecule. Contrary to these observations, FEBID in the UHV setup was found to yield a quantitative loss and desorption of the chlorine from the deposits, an effect that we attribute to electron-induced secondary and tertiary reactions in the deposition process. We find this precursor to be stable at ambient conditions and to have sufficient vapor pressure to be suitable for use in HV instruments. More importantly, in the UHV setup, FEBID with [Au(CH3)2Cl]2 yielded deposits with high gold content, ranging from 45 to 61 atom % depending on the beam current and on the cleanliness of the substrates surface.
CRIS-Team Scopus Importer:2024-12-16
Keywords: dissociative electron attachment; dissociative ionization; focused-electron-beam-induced deposition (FEBID); gold deposit; low-energy electrons; quantum chemical calculation; ultrahigh vacuum

Calcium catalyzed enantioselective intramolecular alkene hydroamination with chiralC2-symmetric bis-amide ligands - Stegner, Philipp; Eyselein, Jonathan; Ballmann, Gerd; Langer, Jens; Schmidt, Jochen; Harder, Sjoerd (Dalton Transactions, 2021)
The chiral building block (R)-(+)-2,2′-diamino-1,1′-binaphthyl, (R)-BINAM, which is often used as backbone in privileged enantioselective catalysts, was converted to a series ofN-substituted proligandsR1-H2(R = CH2tBu, C(H)Ph2, PPh2, dibenzosuberane, 8-quinoline). After double deprotonation with strong Mg or Ca bases, a series of alkaline earth (Ae) metal catalystsR1-Ae·(THF)nwas obtained. Crystal structures of theseC2-symmetric catalysts have been analyzed by quadrant models which show that the ligands with C(H)Ph2, dibenzosuberane and 8-quinoline substituents should give the best steric discrimination for the enantioselective intramolecular alkene hydroamination (IAH) of the aminoalkenes H2C=CHCH2CR′2CH2NH2(CR′2= CPh2, CCy or CMe2). The dianionicR12−ligand inR1-Ae·(THF)nfunctions as reagent that deprotonates the aminoalkene substrate, while the monoanionic (R1-H)−ligand formed in this reaction functions as a chiral spectator ligand that controls the enantioselectivity of the ring closure reaction. Depending on the substituent R in the BINAM ligand, full cyclization of aminoalkenes to chiral pyrrolidine products as fast as 5 minutes was observed. Product analysis furnished enantioselectivities up to 57% ee, which marks the highest enantioselectivity reported for Ca catalyzed IAH. Higher selectivities are impeded by double protonation of theR12−ligand leading to complete loss of chiral information in the catalytically active species.
CRIS-Team Scopus Importer:2021-03-19

Dipyrromethene and beta-Diketinninate Zinc Hydride Complexes: Resemblances and Differences - Ballmann, Gerd; Grams, Samuel; Elsen, Holger; Harder, Sjoerd (Organometallics, 2019)
A new dipyrromethene (DPM) ligand with bulky DIPP-substituents is introduced (DIPP = 2,6-diisopropylphenyl). The ligand, abbreviated as (DPM)-D-DIPP, was deprotonated with ZnEt2 to give ((DPM)-D-DIPP)ZnEt, which reacted with I-2 to form ((DPM)-D-DIPP)ZnI. Reaction of the latter with K[N(Pr-i)HBH3] afforded a labile Zn amidoborane complex which, after beta-hydride elimination, formed ((DPM)-D-DIPP)ZnH. Crystal structures of ((DPM)-D-DIPP)ZnX (X = Et, I, H) revealed their monomeric nature. The Zn-N bond distances are somewhat longer than those in the corresponding, monomeric beta-diketiminate complexes ((BDI)-B-DIPP)ZnX ((BDI)-B-DIPP = CH[C(Me)N-DIPP](2)). This is in agreement with calculated NPA charges, which are lower on the N atoms of DPM compared to those on BDI. Reaction of ((DPM)-D-DIPP)ZnH with CO2 gave ((DPM)-D-DIPP)Zn(O2CH), which crystallized as a monomer with a symmetrically bound eta(2)-formate ligand. In contrast, the beta-diketiminate complex crystallizes as a dimer [((BDI)-B-DIPP)Zn(O2CH)](2) with bridging formate ligands. Reaction of ((DPM)-D-DIPP)Zn(O2CH) with various silanes regenerated the hydride complex ((DPM)-D-DIPP)ZnH. Catalytic CO2 hydrosilylation with (EtO)(3)SiH using ((DPM)-D-DIPP)ZnH as a catalyst gave full reduction to [Si]-OMe species, whereas the catalyst ((BDI)-B-DIPP)ZnH only partially reduced CO2 to [Si]-OC(O)H. The advantage of the (DPM)-D-DIPP ligand is the arrangement of the DIPP-substituents, which form a pocket around the Zn-X unit, preventing dimerization and influencing its reactivity. In addition, in contrast to the negatively charged central backbone carbon in the (BDI)-B-DIPP ligand, that in (DPM)-D-DIPP is neutral. This makes it less nucleophilic and Bronsted basic, as expected for a true spectator ligand.
CRIS-Team WoS Importer:2019-08-09

Heteroleptic Heavier Alkaline Earth Metal Amide Complexes Stabilized by a Superbulky β-Diketiminate Ligand - Gentner, Thomas; Rösch, Bastian; Thum, Katharina; Langer, Jens; Ballmann, Gerd; Pahl, Jürgen; Donaubauer, Wolfgang; Hampel, Frank; Harder, Sjoerd (Organometallics, 2019)
Heteroleptic alkaline earth metal (Ae = Ca, Sr, Ba) amide complexes with the superbulky β-diketiminate ligand DIPePBDI (CH[C(Me)N-DIPeP]2, DIPeP = 2,6-di-iso-pentylphenyl) have been prepared by direct deprotonation of DIPePBDI-H with either AeN′′2 or AeN′′2·(THF)2 (N′′ = N(SiMe3)2). Despite long reaction times of 5-14 days, this convenient one-step synthetic method has the major advantage that metal-pure products are obtained in generally quantitative yields. All (DIPePBDI)AeN′′ and (DIPePBDI)AeN′′·THF complexes are monomeric and stabilized by agostic metal···Me3Si and metal···iso-pentyl interactions. They are highly soluble in toluene and indefinitely stable toward ligand scrambling, even after 2 weeks at 140 °C. The same series with the smaller DIPPBDI ligand (CH[C(Me)N-DIPP]2, DIPP = 2,6-di-iso-propylphenyl) could, except for Ca, also be prepared by direct ligand deprotonation. The (DIPPBDI)CaN′′ and (DIPPBDI)CaN′′·THF complexes are stable toward ligand exchange up to 110 °C. Whereas THF-free (DIPPBDI)SrN′′ and (DIPPBDI)BaN′′ decompose at 50 and 20 °C, respectively, their THF adducts were found to be stable up to 60 °C. This is, however, strongly dependent on complex purity. Slight hydrolysis or contamination with KN′′ accelerates ligand scrambling. Therefore, partial hydrolysis and salt metathesis routes that involve KN′′ should be avoided when synthesizing heteroleptic complexes of the heavier Ae metals.
CRIS-Team Scopus Importer:2019-07-09

Insights into LiAlH4 Catalyzed Imine Hydrogenation - Elsen, Holger; Langer, Jens; Ballmann, Gerd; Wiesinger, Michael; Harder, Sjoerd (Chemistry - A European Journal, 2020)
Commercial LiAlH4 can be used in catalytic quantities in the hydrogenation of imines to amines with H2. Combined experimental and theoretical investigations give deeper insight in the mechanism and identifies the most likely catalytic cycle. Activity is lost when Li in LiAlH4 is exchanged for Na or K. Exchanging Al for B or Ga also led to dramatically reduced activities. This indicates a heterobimetallic mechanism in which cooperation between Li and Al is crucial. Potential intermediates on the catalytic pathway have been isolated from reactions of MAlH4 (M=Li, Na, K) and different imines. Depending on the imine, double, triple or quadruple imine insertion has been observed. Prolonged reaction of LiAlH4 with PhC(H)=NtBu led to a side-reaction and gave the double insertion product LiAlH2[N]2 ([N]=N(tBu)CH2Ph) which at higher temperature reacts further by ortho-metallation of the Ph ring. A DFT study led to a number of conclusions. The most likely catalyst for hydrogenation of PhC(H)=NtBu with LiAlH4 is LiAlH2[N]2. Insertion of a third imine via a heterobimetallic transition state has a barrier of +23.2 kcal mol−1 (ΔH). The rate-determining step is hydrogenolysis of LiAlH[N]3 with H2 with a barrier of +29.2 kcal mol−1. In agreement with experiment, replacing Li for Na (or K) and Al for B (or Ga) led to higher calculated barriers. Also, the AlH4− anion showed very high barriers. Calculations support the experimentally observed effects of the imine substituents at C and N: the lowest barriers are calculated for imines with aryl-substituents at C and alkyl-substituents at N.
CRIS-Team Scopus Importer:2020-12-04
Keywords: DFT; heterobimetallic; hydride; hydrogenation; imine

Lewis acidic alkaline earth metal complexes with a perfluorinated diphenylamide ligand - Fischer, Christian; Rösch, Andreas; Elsen, Holger; Ballmann, Gerd; Wiesinger, Michael; Langer, Jens; Färber, Christian; Harder, Sjoerd (Dalton Transactions, 2019)
Alkaline earth metal (Ae) chemistry with the anion [N(C 6 F 5 ) 2 ] - has been explored. Deprotonation of the amine (C 6 F 5 ) 2 NH, abbreviated in here as N F H, with 0.5 equivalent of AeN′′ 2 (N′′ = N(SiMe 3 ) 2 ) is fast and gave, dependent on the solvent, the complexes AeN F 2 , AeN F 2 ·(THF) 2 and AeN F 2 ·(Et 2 O) 2 (Ae = Mg, Ca, Sr). Using a 1/1 ratio, mixed amide complexes were obtained: N F AeN′′ (Ae = Mg, Ca, Sr). Crystal structures of the monomers AeN F 2 ·(THF) 2 (Ae = Mg, Ca, Sr) and AeN F 2 ·(Et 2 O) 2 (Ae = Mg, Ca) are presented and compared with those of AeN′′ 2 ·(THF) 2 . In addition, crystal structures of the homoleptic dimer (MgN F 2 ) 2 and the heteroleptic dimers (N F AeN′′) 2 (Ae = Mg, Ca, Sr) are discussed. All structures are strongly influenced by very short Ae⋯F contacts down to circa 2.11 Å (Mg), 2.50 Å (Ca) and 2.73 Å (Sr). AIM analysis illustrates that, although Ae⋯F contacts are short, there is no bond-critical-point along this axis, indicating an essentially electrostatic interaction. The monomeric complexes feature strong C 6 F 5 ⋯C 6 F 5 π-stacking, resulting in unusually acute N F -Ae-N F angles as small as 95°. Heteroleptic (N F AeN′′) 2 complexes retain their dimeric structure in C 6 D 6 solution and there is no indication of ligand scrambling by the Schlenk equilibrium, suggesting that an electron withdrawing ligand may stabilize heteroleptic complexes. According to DFT calculations, the heteroleptic arrangement is 70 kJ mol -1 more stable than the homoleptic dimers. The Lewis acidity of MgN F 2 has been quantified with the Gutmann-Beckett method and by calculation of the Fluoride-Ion-Affinity. The latter calculations show that the Lewis acidity of MgN F 2 and CaN F 2 is comparable to that of B(C 6 F 5 ) 3 . Dimeric (MgN F 2 ) 2 fully abstracts Et 3 PO from Et 3 PO·B(C 6 F 5 ) 3 and may have potential in Lewis acid catalysis.
CRIS-Team Scopus Importer:2019-06-04

Low-Coordinate Monomeric Zinc Hydride Complexes with Encapsulating Dipyrromethene Ligands and Reactivity with B(C6F5)3 - Ballmann, Gerd; Martin, Johannes; Langer, Jens; Färber, Christian; Harder, Sjoerd (Zeitschrift für Anorganische und Allgemeine Chemie, 2019)
The dipyrromethene (DPM) ligand is the key to isolation of monomeric Zn hydride complexes with tricoordinate zinc centers. A range of RDPM ligands with various substituents in the pole position (1,9-positions) were prepared: R = tBu, adamantyl (Ad), mesityl (Mes), 2,6-diisopropylphenyl (DIPP), 2,4,6-triphenylphenyl (Mes*), or 9-anthracenyl (Anth). Reaction of the ligands with Et2Zn gave a series of (RDPM)ZnEt complexes, which were converted with I2 to the corresponding (RDPM)ZnI compounds. The latter reacted by salt metathesis with KN(iPr)HBH3 to the series of Zn hydride complexes (RDPM)ZnH. For ligands with the larger Mes* and Anth substituents, (RDPM)ZnEt was converted to (RDPM)ZnOSiPh3, which after reaction with PhSiH3 gave the hydrides. While Zn hydride complexes with R = tBu or Ad are dimeric, all complexes with aryl-substituents are monomeric. The aryl groups span a cavity around the metal, blocking dimerization and causing a high-field shift of the 1H NMR signals due to the ASIS effect. Attempted abstraction of the hydride with B(C6F5)3 led to cleavage of the B-C6F5 bond.
CRIS-Team Scopus Importer:2019-11-15
Keywords: B(C; Dipyrromethene; Hydride; Zinc

Low Valent Magnesium Chemistry with a Super Bulky β-Diketiminate Ligand - Gentner, Thomas; Rösch, Bastian; Ballmann, Gerd; Langer, Jens; Elsen, Holger; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
The steric bulk of the well-known DIPP BDI ligand (CH[C(CH 3 )N-DIPP] 2 , DIPP=2,6-diisopropylphenyl) was increased by replacing isopropyl for isopentyl groups. This very bulky DIPeP BDI ligand could not stabilize the radical species ( DIPeP BDI)Mg . : reduction of ( DIPeP BDI)MgI with Na gave ( DIPeP BDI) 2 Mg 2 with a rather long Mg-Mg bond of 3.0513(8) Å. Addition of TMEDA prior to reduction gave complex ( DIPeP BDI) 2 Mg 2 (C 6 H 6 ), which could also be obtained as its THF adduct. It is speculated that combination of a bulky spectator ligand and TMEDA prevents dimerization of the intermediate Mg I radical, which then reacts with the benzene solvent. Complex ( DIPeP BDI) 2 Mg 2 (C 6 H 6 ), which formally contains the anti-aromatic anion C 6 H 6 2− , reacted with tBuOH as a Brønsted base to 1,3- and 1,4-cyclohexadiene and with H 2 as a two electron donor to ( DIPeP BDI) 2 Mg 2 H 2 and C 6 H 6 . It also reductively cleaved the C−F bond in fluorobenzene and gave ( DIPeP BDI)MgPh, ( DIPeP BDI)MgF, and C 6 H 6 .
CRIS-Team Scopus Importer:2019-08-16
Keywords: alkaline earth metal; bulky ligand; low valence; magnesium; metal-metal bonding

Magnesium Cyanide or Isocyanide? - Ballmann, Gerd; Elsen, Holger; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
Preference for the binding mode of the CN- ligand to Mg (Mg-CN vs. Mg-NC) is investigated. A monomeric Mg complex with a terminal CN ligand was prepared using the dipyrromethene ligand (DPM)-D-Mes which successfully blocks dimerization. While reaction of ((DPM)-D-Mes)MgN(SiMe3)(2) with Me3SiCN gave the coordination complex ((DPM)-D-Mes)MgN(SiMe3)(2).NCSiMe3, reaction with ((DPM)-D-Mes)Mg(nBu) led to ((DPM)-D-Mes)MgNC.(THF)(2). A Mg-NC/Mg-CN ratio of approximate to 95:5 was established by crystal-structure determination and DFT calculations. IR studies show absorbances for CN stretching at 2085 cm(-1) (Mg-NC) and 2162 cm(-1) (Mg-CN) as confirmed by C-13 labeling. In solution and in the solid state, the CN ligand rotates within the pocket. The calculated isomerization barrier is only 12.0 kcal mol(-1) and the C-13 NMR signal for CN decoalesces at -85 degrees C (Mg-NC: 175.9 ppm, Mg-CN: 144.3 ppm). Experiment and theory both indicate that Mg complexes with the CN- ligand should not be named cyanides but are more properly defined as isocyanides.
CRIS-Team WoS Importer:2019-10-08

On the Electron-Induced Reactions of (CH3)AuP(CH3)(3): A Combined UHV Surface Science and Gas-Phase Study - Kamali, Ali; Bilgilisoy, Elif; Wolfram, Alexander; Gentner, Thomas; Ballmann, Gerd; Harder, Sjoerd; Marbach, Hubertus; Ingolfsson, Oddur (Nanomaterials, 2022)
Focused-electron-beam-induced deposition (FEBID) is a powerful nanopatterning technique where electrons trigger the local dissociation of precursor molecules, leaving a deposit of non-volatile dissociation products. The fabrication of high-purity gold deposits via FEBID has significant potential to expand the scope of this method. For this, gold precursors that are stable under ambient conditions but fragment selectively under electron exposure are essential. Here, we investigated the potential gold precursor (CH3)AuP(CH3)(3) using FEBID under ultra-high vacuum (UHV) and spectroscopic characterization of the corresponding metal-containing deposits. For a detailed insight into electron-induced fragmentation, the deposit's composition was compared with the fragmentation pathways of this compound through dissociative ionization (DI) under single-collision conditions using quantum chemical calculations to aid the interpretation of these data. Further comparison was made with a previous high-vacuum (HV) FEBID study of this precursor. The average loss of about 2 carbon and 0.8 phosphor per incident was found in DI, which agreed well with the carbon content of the UHV FEBID deposits. However, the UHV deposits were found to be as good as free of phosphor, indicating that the trimethyl phosphate is a good leaving group. Differently, the HV FEBID experiments showed significant phosphor content in the deposits.
CRIS-Team WoS Importer:2022-08-26

s-Block Metal Dibenzoazepinate Complexes: Evidence for Mg-Alkene Encapsulation - Freitag, Benjamin; Elsen, Holger; Pahl, Jürgen; Ballmann, Gerd; Herrera, Alberto Cesar; Dorta, Romano; Harder, Sjoerd (Organometallics, 2017)

Stabilization of Heteroleptic Heavier Alkaline Earth Metal Complexes with an Encapsulating Dipyrromethene Ligand - Ballmann, Gerd; Rösch, Bastian; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2019)
A new dipyrromethene ligand with 9-anthracenyl substituents for steric shielding of the metal has been introduced. The ligand, AnthDPM-H (3), was directly deprotonated with MN′′2 M = Mg, Ca, Sr, Ba, Zn; N′′ = N(SiMe3)2 to give (AnthDPM)MN′′ (4–8) in the form of highly fluorescent substances that are intensively colored from deep-red to purple. Crystal structures reveal in all cases monomeric complexes with tricoordinate metals. Also the crystal structure of (AnthDPM)K, prepared by reaction of 3 with KN′′, is presented. The metal's coordination sphere in complexes 4–8 is further saturated by anagostic M···MeSi interactions which are most important for the smaller metals Mg and Zn. For the larger metals, Ca–Ba, the anthracenyl-substituents assist in metal coordination. These secondary metal π-interactions result in very high thermal stabilities. The least stable complex (AnthDPM)BaN′′ decomposes at circa 100 °C. The dipyrromethene complexes are clearly more stable than the corresponding β-diketiminate complexes (DIPPBDI)MN′′ DIPPBDI = CH[C(Me)N-DIPP]2, DIPP =2,6-diisopropylphenyl which partially decompose at room temperature. These heteroleptic complexes of similar constitution, with metals ranging from Mg to Ba, form a new series that is potentially useful for investigations towards metal effects in early main group metal catalysis.
CRIS-Team Scopus Importer:2019-08-23
Keywords: Alkaline earth metals; Heteroleptic complexes; Ligand design; Thermal stability; Zinc